Electrode material and preparation method thereof, electrode plate, battery and electric device
By using a core-shell structure and an ion-conducting polymer cladding layer in the battery electrode material, the reaction problem caused by contact between the electrode active material and the electrolyte is solved, and the cycle performance of the battery and the stability of the cladding layer are improved.
Patent Information
- Application Number
- CN202311352426.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-10-18
- Publication Date
- 2025-04-18
AI Technical Summary
The electrode active material in the battery is prone to react when it comes into contact with the electrolyte, affecting the material activity and reducing the capacity and circulation performance of the battery.
The electrode material adopts a core-shell structure to form an ion-conducting polymer through a polymer monomer containing carboxyl groups and hydroxy groups, and coats the electrode active material in situ to reduce contact with the electrolyte.
The reaction between the electrode active material and the electrolyte is effectively reduced, the circulation performance of the battery is improved, and the stability of the cladding layer and the core structure is improved through the formation of chemical bonds.
Smart Images

Figure CN119852335A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the field of battery technology, and in particular to electrode materials and preparation methods thereof, electrode sheets, batteries and electrical devices. Background Art
[0002] The electrode materials in the battery include positive electrode materials and negative electrode materials. When in contact with the electrolyte, the positive electrode active materials and the negative electrode active materials easily react with the electrolyte, affecting the activity of the active materials, thereby reducing the capacity and cycle performance of the battery. Summary of the invention
[0003] The present application is made in view of the above-mentioned problems, and its purpose is to provide an electrode material that reduces the contact between the active material and the electrolyte and improves the cycle performance of the battery.
[0004] In order to achieve the above-mentioned objectives, the embodiments of the present application provide an electrode material and a preparation method thereof, an electrode sheet, a battery and an electrical device.
[0005] In a first aspect, an embodiment of the present application proposes an electrode material, comprising a core and a coating layer at least partially coating the surface of the core, wherein the core comprises an electrode active material, and the coating layer comprises a polymer mainly formed by at least one polymer monomer; the polymer monomer comprises a carboxyl group and a hydroxyl group; or, the polymer monomer comprises an amino group and a hydroxyl group.
[0006] Thus, in the technical scheme of the embodiment of the present application, by setting the electrode material into a core-shell structure, the carboxyl group and the hydroxyl group can spontaneously form an ion-conducting polymer through a polymer monomer containing a carboxyl group and a hydroxyl group, thereby realizing in-situ coating of the electrode active material, thereby coating the electrode active material in the coating layer, thereby reducing the contact between the electrode active material and the electrolyte, thereby reducing the reaction between the electrode active material and the electrolyte, and improving the cycle performance of the battery. Or by spontaneously forming an ion-conducting polymer through the amino group and the hydroxyl group of the polymer monomer containing an amino group and a hydroxyl group, thereby realizing in-situ coating of the electrode active material, thereby coating the electrode active material in the coating layer, thereby reducing the contact between the electrode active material and the electrolyte, thereby reducing the reaction between the electrode active material and the electrolyte, and improving the cycle performance of the battery. In the present application, what is formed between the coating layers is the effect of chemical bonding, and the structure of the coating layer and the inner core is more stable, which improves the stability of the structure of the coating layer and the inner core active material.
[0007] It should be noted that in the embodiments of the present application, the electrode material can be either a positive electrode material or a negative electrode material, and the positive electrode active material can be formed into a core-shell structure coated with a polymer monomer in the positive electrode material to reduce the contact between the positive electrode active material and the electrolyte. It can also be formed into a core-shell structure coated with a polymer monomer in the negative electrode material to reduce the contact between the negative electrode active material and the electrolyte.
[0008] In any embodiment, the polymer monomer comprises a carboxyl group and a hydroxyl group, wherein:
[0009] The number of the carboxyl groups is m1, and m1 is a positive integer of 1 to 5. When m1 is 1 to 5, it can provide sufficient carboxyl groups to react with hydroxyl groups to form polymers, and can also reduce the mass proportion of the coating layer, reduce the impact on the mass proportion of the active material, and affect the impact on the energy density; optionally, m1 is a positive integer of 1 to 3, which can further reduce the mass proportion of the coating layer and reduce the impact on the mass proportion of the active material; and / or,
[0010] The number of hydroxyl groups is n1, and n1 is a positive integer of 1 to 7. When n1 is a positive integer of 1 to 7, it can not only provide sufficient hydroxyl groups to react with carboxyl groups to form polymers, but also reduce the mass proportion of the coating layer, reduce the impact on the mass proportion of the active material, and affect the impact on the energy density; optionally, n1 is a positive integer of 3 to 5, which can further reduce the mass proportion of the coating layer and reduce the impact on the mass proportion of the active material.
[0011] In any embodiment, the polymer monomer includes but is not limited to at least one of sodium alginate, (1-pyrenyl)-BD-glucuronide, D-galacturonic acid and glycyrrhizic acid. The use of at least one of the above polymer monomers can further increase the mass proportion of active materials while fully polymerizing, thereby increasing the energy density of the battery.
[0012] In any embodiment, the polymer monomer comprises an amino group and a hydroxyl group, wherein:
[0013] The number of amino groups is m2, where m2 is a positive integer of 1 to 5, which can provide sufficient amino groups to react with hydroxyl groups to form polymers, and can also reduce the mass proportion of the coating layer, reduce the impact on the mass proportion of the active material, and affect the impact on the energy density; optionally, m2 is a positive integer of 2 to 3, which can further reduce the mass proportion of the coating layer and reduce the impact on the mass proportion of the active material; and / or,
[0014] The number of hydroxyl groups is n2, where n2 is a positive integer of 1 to 6, which can not only provide sufficient hydroxyl groups to react with amino groups to form polymers, but also reduce the mass proportion of the coating layer, reduce the impact on the mass proportion of active materials, and affect the impact on energy density; optionally, n2 is a positive integer of 2 to 4, which can further reduce the mass proportion of the coating layer and reduce the impact on the mass proportion of active materials.
[0015] In any embodiment, the polymer monomer includes but is not limited to at least one of diglycolamine, 1-amino-3-ethoxy-2-propanol, naphthol AS-BI N-acetyl-B-D-aminoglucosidoside and 1-[2-(2-hydroxyethoxy)ethyl]piperazine. The use of at least one of the above amino groups and hydroxyl groups can further increase the mass proportion of active materials while fully polymerizing, thereby increasing the energy density of the battery.
[0016] In any embodiment, the electrode material includes a compound containing multivalent metal ions. The multivalent metal ions can provide coordination bonds for the polymerization reaction of polymer monomers, increase the polymerization rate of polymer monomers, and increase the coverage rate of the active material of the core.
[0017] In any embodiment, the compound containing multivalent metal ions includes but is not limited to a compound containing at least one of iron ions, aluminum ions, manganese ions and nickel ions. The use of the above-mentioned compound containing multivalent metal ions can further provide coordination bonds for the polymerization of polymer monomers, increase the polymerization rate of polymer monomers, and increase the coverage rate of the active material of the inner core.
[0018] In any embodiment, the electrode material is a positive electrode material, wherein the material of the inner core includes at least lithium manganese oxide. By setting the positive electrode active material to lithium manganese oxide, multivalent metal manganese can be used to provide coordination bonds for the polymerization of polymer monomers. At the same time, the polymer coating layer formed by the polymer monomers can also be coated on the surface of the lithium manganese oxide, reducing the contact between the lithium manganese oxide and the electrolyte, reducing the dissolution of manganese ions, and thereby improving the cycle performance of the battery.
[0019] In any embodiment, the lithium manganate includes doped lithium manganate, and the molecular formula of the doped lithium manganate includes LiMn 2-α X α O4;
[0020] Wherein, X includes at least one of magnesium, cobalt, nickel, chromium, iron and titanium.
[0021] The value of α is in the range of 0.001-0.5.
[0022] In any embodiment, the mass fraction of the coating layer is w1, and the mass fraction of the core is w2, wherein,
[0023] 0.05%≤w1:(w1+w2)≤1%, the mass proportion of the coating layer in the electrode material is 0.05%~1%, which can make the thickness of the coating layer appropriate, which is beneficial to the rapid transmission of ions and electrons of the electrode material, reduces the impact on the battery energy density, and reduces the direct contact between the active material and the electrolyte; optionally, 0.1%≤w1:(w1+w2)≤0.5%, which can further facilitate the rapid transmission of ions and electrons of the electrode material, reduce the impact on the battery energy density, and reduce the direct contact between the active material and the electrolyte.
[0024] In a second aspect, the present application provides a method for preparing an electrode material, comprising the following steps:
[0025] Forming a coating layer outside the inner core, wherein the coating layer is formed with a polymer formed from at least one polymer monomer, to obtain an electrode material;
[0026] wherein the polymer monomer comprises a carboxyl group and a hydroxyl group; or,
[0027] The polymer monomers include amino groups and hydroxyl groups.
[0028] By forming a coating layer outside the inner core, the active material of the inner core can be coated to form a coating layer structure, thereby reducing the direct contact between the active material of the inner core and the electrolyte and improving the battery cycle performance.
[0029] In any embodiment, the step of forming a coating layer outside the core, wherein the coating layer is formed with a polymer formed from at least one polymer monomer, and obtaining the electrode material comprises:
[0030] The polymer monomer is polymerized on the surface of lithium manganate to form a coating layer to obtain an electrode material.
[0031] By polymerizing the polymer monomer on the surface of lithium manganate to form a coating layer, the carboxylate functional groups and carboxyl groups can be spontaneously polymerized on the outer layer of the inner core to form an in-situ coating layer for the inner core material, thereby reducing the direct contact between the active material of the inner core and the electrolyte.
[0032] In other embodiments of the present application, the amino groups and hydroxyl groups can also be polymerized on the surface of lithium manganate to form a coating layer, so that the amino groups and hydroxyl groups in the compounds containing amino groups and hydroxyl groups spontaneously polymerize in the outer layer of the inner core to form an in-situ coating layer for the inner core material, thereby reducing the direct contact between the active material of the inner core and the electrolyte.
[0033] In any embodiment, the step of polymerizing the polymer monomer on the surface of lithium manganate to form a coating layer to obtain the electrode material comprises:
[0034] The sodium alginate solution is mixed with lithium manganate, and a coating layer is formed on the surface of the lithium manganate by polymerization reaction to obtain an electrode material.
[0035] By mixing a sodium alginate solution with a lithium manganate solution and performing a polymerization reaction on the surface of the lithium manganate to form a coating layer, sodium alginate can spontaneously form a polymer coating layer on the surface of the lithium manganate under the action of the coordination bond of manganese ions. At the same time, the polymer coating layer formed by sodium alginate can also reduce the dissolution of manganese ions, thereby improving the cycle performance of the battery.
[0036] In any embodiment, the polymerization reaction time is 0.5 to 5 hours. The polymerization reaction time affects the polymerization effect. The polymerization reaction time of 0.5 to 5 hours can make the polymerization reaction more complete, improve the coating effect of the coating layer, and ensure the production efficiency; optionally, the polymerization reaction time is 1 to 2 hours, which can further make the polymerization reaction more complete, improve the coating effect of the coating layer, and ensure the production efficiency; and / or,
[0037] The polymerization reaction temperature is 10-45° C., which can improve the polymerization reaction efficiency and reduce the probability of side reactions. Optionally, the polymerization reaction time is 20-35° C., which can further improve the polymerization reaction efficiency and reduce the probability of side reactions.
[0038] In a third aspect, an embodiment of the present application provides an electrode sheet, comprising an electrode material according to the first aspect of the present application or an electrode material prepared by the preparation method of the electrode material according to the second aspect of the present application.
[0039] In a fourth aspect, an embodiment of the present application provides a battery, comprising the electrode sheet of the third aspect of the present application.
[0040] In a fifth aspect, an embodiment of the present application proposes an electrical device, comprising the battery of the fourth aspect of the present application. BRIEF DESCRIPTION OF THE DRAWINGS
[0041] Figure 1 is a schematic diagram of a secondary battery according to one embodiment of the present application.
[0042] Figure 2 yes Figure 1 An exploded view of a secondary battery according to an embodiment of the present application is shown.
[0043] Figure 3 is a schematic diagram of a battery module according to an embodiment of the present application.
[0044] Figure 4 It is a schematic diagram of a battery pack according to one embodiment of the present application.
[0045] Figure 5 yes Figure 4An exploded view of a battery pack according to an embodiment of the present application is shown.
[0046] Figure 6 Schematic diagram of an electrical device using a secondary battery according to an embodiment of the present application as a power source.
[0047] Description of reference numerals:
[0048] 1 battery pack; 2 upper box; 3 lower box; 4 battery module; 5 secondary battery; 51 shell; 52 electrode assembly; 53 top cover assembly. DETAILED DESCRIPTION
[0049] The following specifically discloses the embodiments of the electrode material and preparation method thereof, electrode sheet, battery and electrical device of the present application. However, there may be cases where unnecessary detailed descriptions are omitted. For example, there are cases where detailed descriptions of well-known matters and repeated descriptions of actually the same structure are omitted. This is to avoid the following description from becoming unnecessarily lengthy and to facilitate the understanding of those skilled in the art. In addition, the drawings and the following description are provided for those skilled in the art to fully understand the present application and are not intended to limit the subject matter described in the claims.
[0050] "Scope" disclosed in the present application is limited in the form of lower limit and upper limit, and a given range is limited by selecting a lower limit and an upper limit, and the selected lower limit and upper limit define the boundary of a special range. The scope limited in this way can be including end values or not including end values, and can be arbitrarily combined, that is, any lower limit can be combined with any upper limit to form a scope. For example, if the scope of 60-120 and 80-110 is listed for a specific parameter, it is understood that the scope of 60-110 and 80-120 is also expected. In addition, if the minimum range values 1 and 2 are listed, and if the maximum range values 3, 4 and 5 are listed, the following scope can be all expected: 1-3, 1-4, 1-5, 2-3, 2-4 and 2-5. In the present application, unless otherwise specified, the numerical range "ab" represents the abbreviation of any real number combination between a and b, wherein a and b are real numbers. For example, the numerical range "0-5" means that all real numbers between "0-5" are listed in this document, and "0-5" is just an abbreviation of these numerical combinations. In addition, when a parameter is expressed as an integer ≥ 2, it is equivalent to disclosing that the parameter is, for example, an integer of 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, etc.
[0051] Unless otherwise specified, all embodiments and optional embodiments of the present application can be combined with each other to form a new technical solution.
[0052] Unless otherwise specified, all technical features and optional technical features of this application can be combined with each other to form a new technical solution.
[0053] If there is no special explanation, all steps of the present application can be performed sequentially or randomly, preferably sequentially. For example, the method includes steps (a) and (b), which means that the method may include steps (a) and (b) performed sequentially, or may include steps (b) and (a) performed sequentially. For example, the method may further include step (c), which means that step (c) may be added to the method in any order. For example, the method may include steps (a), (b) and (c), or may include steps (a), (c) and (b), or may include steps (c), (a) and (b), etc.
[0054] The electrode materials in the battery include positive electrode materials and negative electrode materials. When in contact with the electrolyte, the positive electrode active materials and the negative electrode active materials easily react with the electrolyte, affecting the activity of the active materials, thereby reducing the capacity and cycle performance of the battery.
[0055] Therefore, there are endless technologies for improving the direct contact between active materials and electrolytes. For example, a positive electrode of a lithium manganese oxide battery has a higher specific capacity and good cycle performance by using a lithium manganese oxide positive electrode material coated with tin oxide, and has better high-temperature cycle performance. The tin oxide coating layer is more dense, and the tin oxide layer can still maintain a good fit with the main lithium manganese oxide material during a long-term cycle, and it is not easy to separate. Therefore, the outer layer of tin oxide can maintain the protection of the internal lithium manganese oxide for a long time, prevent the external HF from corroding the lithium manganese oxide, and effectively improve the cycle stability of the material. A network γ-alumina coated modified graphite negative electrode material, its preparation method and its application, by uniformly coating aluminum salt on the surface of a commercial graphite negative electrode through a sol-gel method; vacuum drying the obtained coated precursor; the dried product is subjected to a high-temperature calcination reaction to obtain a network γ-alumina coated modified graphite material; the process is simple, the conditions are mild and the cost is low, and the surface of the network γ-alumina coated modified graphite negative electrode material is uniformly coated and the particle size distribution is uniform. However, since the coating layer is usually coated on the surface of the core by high-temperature calcination treatment, the production cost is greatly increased. The coating layer and the core only rely on physical interaction, and its structural stability needs to be further improved.
[0056] Unexpectedly, by forming a polymer coating on the surface of the electrode active material, the direct contact between the electrode active material and the electrolyte can be reduced. At the same time, the polymer monomers can spontaneously form polymers, which greatly reduces the production cost. In addition, since the polymer monomers are combined into polymers by chemical bonds, the structure is more stable, which improves the stability of the coating layer and the core active material structure, thereby improving the cycle performance of the battery.
[0057] In a first aspect, an embodiment of the present application proposes an electrode material, comprising a core and a coating layer at least partially coating the surface of the core, wherein the core comprises an electrode active material, and the coating layer comprises a polymer mainly formed by at least one polymer monomer; the polymer monomer comprises a carboxyl group and a hydroxyl group; or, the polymer monomer comprises an amino group and a hydroxyl group.
[0058] Thus, in the technical scheme of the embodiment of the present application, by setting the electrode material into a core-shell structure, the carboxyl group and the hydroxyl group can spontaneously form an ion-conducting polymer through a polymer monomer containing a carboxyl group and a hydroxyl group, thereby realizing in-situ coating of the electrode active material, thereby coating the electrode active material in the coating layer, thereby reducing the contact between the electrode active material and the electrolyte, thereby reducing the reaction between the electrode active material and the electrolyte, and improving the cycle performance of the battery. Or by spontaneously forming an ion-conducting polymer through the amino group and the hydroxyl group of the polymer monomer containing an amino group and a hydroxyl group, thereby realizing in-situ coating of the electrode active material, thereby coating the electrode active material in the coating layer, thereby reducing the contact between the electrode active material and the electrolyte, thereby reducing the reaction between the electrode active material and the electrolyte, and improving the cycle performance of the battery. In the present application, what is formed between the coating layers is the effect of chemical bonding, and the structure of the coating layer and the inner core is more stable, which improves the stability of the structure of the coating layer and the inner core active material.
[0059] It should be noted that in the embodiments of the present application, the electrode material can be either a positive electrode material or a negative electrode material, and the positive electrode active material can be formed into a core-shell structure coated with a polymer monomer in the positive electrode material to reduce the contact between the positive electrode active material and the electrolyte. It can also be formed into a core-shell structure coated with a polymer monomer in the negative electrode material to reduce the contact between the negative electrode active material and the electrolyte.
[0060] In any embodiment, the polymer monomer comprises a carboxyl group and a hydroxyl group, wherein:
[0061] The number of the carboxyl groups is m1, and m1 is a positive integer of 1 to 5. When m1 is 1 to 5, it can provide sufficient carboxyl groups to react with hydroxyl groups to form polymers, and can also reduce the mass proportion of the coating layer, reduce the impact on the mass proportion of the active material, and affect the impact on the energy density. The value of m1 can be 1, 2, 3, 4 or 5; optionally, m1 is a positive integer of 1 to 3, which can further reduce the mass proportion of the coating layer and reduce the impact on the mass proportion of the active material; and / or,
[0062] The number of hydroxyl groups is n1, and n1 is a positive integer of 1 to 7. When n1 is a positive integer of 1 to 7, it can not only provide sufficient hydroxyl groups to react with carboxyl groups to form polymers, but also reduce the mass proportion of the coating layer, reduce the impact on the mass proportion of the active material, and affect the impact on the energy density. The value of n1 can be 1, 2, 3, 4, 5, 6 or 7; optionally, n1 is a positive integer of 3 to 5, which can further reduce the mass proportion of the coating layer and reduce the impact on the mass proportion of the active material.
[0063] In any embodiment, the polymer monomer includes but is not limited to at least one of sodium alginate, (1-pyrenyl)-BD-glucuronide, D-galacturonic acid and glycyrrhizic acid. The use of at least one of the above polymer monomers can further increase the mass proportion of active materials while fully polymerizing, thereby increasing the energy density of the battery.
[0064] In any embodiment, the polymer monomer comprises an amino group and a hydroxyl group, wherein
[0065] The number of amino groups is m2, and m2 is a positive integer of 1 to 5, which can not only provide sufficient amino groups to react with hydroxyl groups to form polymers, but also reduce the mass proportion of the coating layer, reduce the impact on the mass proportion of the active material, and affect the impact on the energy density; the value of m2 can be 1, 2, 3, 4 or 5; optionally, m2 is a positive integer of 2 to 3, which can further reduce the mass proportion of the coating layer and reduce the impact on the mass proportion of the active material; and / or,
[0066] The number of the carboxyl groups is n2, and n2 is a positive integer of 1 to 6. It can not only provide sufficient hydroxyl groups to react with amino groups to form polymers, but also reduce the mass proportion of the coating layer, reduce the impact on the mass proportion of the active material, and affect the impact on the energy density. The value of n2 can be 1, 2, 3, 4, 5 or 6; optionally, n2 is a positive integer of 2 to 4, which can further reduce the mass proportion of the coating layer and reduce the impact on the mass proportion of the active material.
[0067] In any embodiment, the polymer monomer includes but is not limited to at least one of diglycolamine, 1-amino-3-ethoxy-2-propanol, naphthol AS-BI N-acetyl-B-D-aminoglucosidoside and 1-[2-(2-hydroxyethoxy)ethyl]piperazine. The use of at least one of the above amino groups and hydroxyl groups can further increase the mass proportion of active materials while fully polymerizing, thereby increasing the energy density of the battery.
[0068] In any embodiment, the electrode material includes a compound containing a polyvalent metal ion. The polyvalent metal ion can provide a coordination bond for the polymerization reaction of the polymer monomer, increase the polymerization rate of the polymer monomer, and increase the coating rate of the active material of the core. In some embodiments of the present application, the compound of the polyvalent metal ion can be in the core, in some embodiments of the present application, the compound of the polyvalent metal ion can be in the coating layer, and in some embodiments of the present application, the compound of the polyvalent metal ion can provide a coordination bond in the solution of the reaction. Preferably, the compound containing the polyvalent metal ion in the core can provide a better coating effect for the core.
[0069] In any embodiment, the compound containing multivalent metal ions includes but is not limited to a compound containing at least one of iron ions, aluminum ions, manganese ions and nickel ions. The use of the above-mentioned compound containing multivalent metal ions can further provide coordination bonds for the polymerization of polymer monomers, increase the polymerization rate of polymer monomers, and increase the coverage rate of the active material of the inner core.
[0070] In any embodiment, the electrode material is a positive electrode material, wherein the material of the inner core includes at least lithium manganese oxide. By setting the positive electrode active material to lithium manganese oxide, multivalent metal manganese can be used to provide coordination bonds for the polymerization of polymer monomers. At the same time, the polymer coating layer formed by the polymer monomers can also be coated on the surface of the lithium manganese oxide, reducing the contact between the lithium manganese oxide and the electrolyte, reducing the dissolution of manganese ions, and thereby improving the cycle performance of the battery.
[0071] In any embodiment, the lithium manganate includes doped lithium manganate, and the molecular formula of the doped lithium manganate includes LiMn 2-α X α O4;
[0072] Wherein, X includes at least one of magnesium, cobalt, nickel, chromium, iron and titanium.
[0073] The value of α is 0.001-0.5.
[0074] It should be noted that in the embodiments of the present application, the chemical formula of lithium manganese oxide is the chemical formula of the material used in the preparation process. In the positive electrode sheet, battery cell, and electrical equipment, due to the formation and circulation processes, those skilled in the art can understand that the elements in the chemical formula of lithium manganese oxide may be lost. For example, the O element will be consumed, so there will be a decrease in the O element in the measured lithium manganese oxide.
[0075] It should be noted that in the positive electrode sheets, battery cells, and electrical equipment, lithium ions will be consumed during the formation and circulation processes, so the measured lithium content in the positive electrode active material will decrease. At the same time, if the positive and negative electrode sheets are supplemented with lithium, after the formation and circulation processes, the measured lithium content in the positive electrode active material will increase.
[0076] In any embodiment, the mass fraction of the coating layer is w1, and the mass fraction of the core is w2, wherein,
[0077] 0.05%≤w1:(w1+w2)≤1%. When the mass proportion of the coating layer in the electrode material exceeds 1%, the coating layer will be too thick, which is not conducive to the rapid transmission of ions and electrons in the electrode material and affects the energy density of the battery. When the mass proportion of the coating layer in the electrode material is less than 0.05%, the coating effect is not good, and the effect of reducing the contact between the active material and the electrolyte is not good. The value of w1:(w1+w2) can be 0.05%, 0.1%, 0.15%, 0.2%, 0.25%, 0.3%, 0.35%, 0.4%, 0.45%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9% or 1%; optionally, 0.1%≤w1:(w1+w2)≤0.5%.
[0078] In a second aspect, the present application provides a method for preparing an electrode material, comprising the following steps:
[0079] Forming a coating layer outside the inner core, wherein the coating layer is formed with a polymer formed from at least one polymer monomer, to obtain an electrode material;
[0080] wherein the polymer monomer comprises a carboxyl group and a hydroxyl group; or,
[0081] The polymer monomers include amino groups and hydroxyl groups.
[0082] By forming a coating layer outside the inner core, the active material of the inner core can be coated to form a coating layer structure, thereby reducing the direct contact between the active material of the inner core and the electrolyte and improving the battery cycle performance.
[0083] In any embodiment, the step of forming a coating layer outside the core, wherein the coating layer is formed with a polymer formed from at least one polymer monomer, and obtaining the electrode material comprises:
[0084] The polymer monomer is polymerized on the surface of lithium manganate to form a coating layer to obtain an electrode material.
[0085] By polymerizing the polymer monomer on the surface of lithium manganate to form a coating layer, the carboxyl groups and hydroxyl groups can be spontaneously polymerized on the outer layer of the inner core to form an in-situ coating layer for the inner core material, thereby reducing the direct contact between the active material of the inner core and the electrolyte.
[0086] In other embodiments of the present application, the amino groups and hydroxyl groups can also be polymerized on the surface of lithium manganate to form a coating layer, so that the amino groups and hydroxyl groups in the compounds containing amino groups and hydroxyl groups spontaneously polymerize in the outer layer of the inner core to form an in-situ coating layer for the inner core material, thereby reducing the direct contact between the active material of the inner core and the electrolyte.
[0087] In any embodiment, the step of polymerizing the polymer monomer on the surface of lithium manganate to form a coating layer to obtain the electrode material comprises:
[0088] The sodium alginate solution is mixed with lithium manganate, and a coating layer is formed on the surface of the lithium manganate by polymerization reaction to obtain an electrode material.
[0089] By mixing a sodium alginate solution with a lithium manganate solution and performing a polymerization reaction on the surface of the lithium manganate to form a coating layer, sodium alginate can spontaneously form a polymer coating layer on the surface of the lithium manganate under the action of the coordination bond of manganese ions. At the same time, the polymer coating layer formed by sodium alginate can also reduce the dissolution of manganese ions, thereby improving the cycle performance of the battery.
[0090] In any embodiment, the polymerization reaction time is 0.5 to 5 hours. The polymerization reaction time affects the polymerization effect. The polymerization reaction time is 0.5 to 5 hours, which can make the polymerization reaction more complete, improve the coating effect of the coating layer, and ensure the production efficiency. The polymerization reaction time can be 0.5 hours, 1 hour, 1.5 hours, 2 hours, 2.5 hours, 3 hours, 3.5 hours, 4 hours, 4.5 hours or 5 hours; optionally, the polymerization reaction time is 1 to 2 hours, which can further make the polymerization reaction more complete, improve the coating effect of the coating layer, and ensure the production efficiency; and / or,
[0091] The polymerization reaction temperature is 10-45°C, which can not only improve the efficiency of the polymerization reaction but also reduce the probability of side reactions. The polymerization reaction temperature can be 10°C, 15°C, 20°C, 25°C, 30°C, 35°C, 40°C or 45°C; optionally, the polymerization reaction time is 20-35°C, which can further improve the efficiency of the polymerization reaction and reduce the probability of side reactions.
[0092] In a third aspect, an embodiment of the present application provides an electrode sheet, comprising an electrode material according to the first aspect of the present application or an electrode material prepared by the preparation method of the electrode material according to the second aspect of the present application.
[0093] In some embodiments of the present application, the electrode sheet includes an electrode slurry, and the electrode slurry includes a conductive agent, a binder, and an electrode material. The mass ratio of the conductive agent, the binder, and the electrode material is (0.5-20): (0.5-10): (70-99). The appropriate mass ratio of the conductive agent, the binder, and the electrode material can improve the cycle performance of the battery while ensuring the battery energy density. Optionally, the mass ratio of the conductive agent, the binder, and the electrode material is (1-2): (1.5-2.5): (94.5-96.5).
[0094] In some embodiments of the present application, the electrode sheet includes a negative electrode sheet, and the negative electrode sheet includes a negative electrode current collector and a negative electrode film layer disposed on at least one surface of the negative electrode current collector, wherein the negative electrode film layer includes a negative electrode active material.
[0095] As an example, the negative electrode current collector has two surfaces opposite to each other in its thickness direction, and the negative electrode film layer is disposed on any one or both of the two opposite surfaces of the negative electrode current collector.
[0096] In some embodiments, the negative electrode current collector may be a metal foil or a composite current collector. For example, as the metal foil, copper foil may be used. The composite current collector may include a polymer material base layer and a metal layer formed on at least one surface of the polymer material substrate. The composite current collector may be formed by forming a metal material (copper, copper alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy, etc.) on a polymer material substrate (such as a substrate of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE), etc.).
[0097] In some embodiments, the negative electrode film layer may further include a binder. The binder may be selected from at least one of styrene-butadiene rubber (SBR), polyacrylic acid (PAA), sodium polyacrylate (PAAS), polyacrylamide (PAM), polyvinyl alcohol (PVA), sodium alginate (SA), polymethacrylic acid (PMAA) and carboxymethyl chitosan (CMCS).
[0098] In some embodiments, the negative electrode film layer may further include a conductive agent, which may be selected from at least one of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene and carbon nanofibers.
[0099] In some embodiments, the negative electrode film layer may optionally include other additives, such as a thickener (eg, sodium carboxymethyl cellulose (CMC-Na)).
[0100] In some embodiments, the negative electrode sheet can be prepared in the following manner: the components for preparing the negative electrode sheet, such as the negative electrode active material, the conductive agent, the binder and any other components are dispersed in a solvent (such as deionized water) to form a negative electrode slurry; the negative electrode slurry is coated on the negative electrode collector, and after drying, cold pressing and other processes, the negative electrode sheet can be obtained.
[0101] In some embodiments of the present application, the electrode sheet includes a positive electrode sheet, the positive electrode sheet includes a positive electrode collector and a positive electrode film layer arranged on at least one surface of the positive electrode collector, and the positive electrode film layer includes the positive electrode material of the first aspect of the present application or the positive electrode material prepared by the preparation method of the positive electrode material of the second aspect of the present application.
[0102] As an example, the positive electrode current collector has two surfaces opposite to each other in its thickness direction, and the positive electrode film layer is disposed on any one or both of the two opposite surfaces of the positive electrode current collector.
[0103] In some embodiments, the positive electrode current collector may be a metal foil or a composite current collector. For example, aluminum foil may be used as the metal foil. The composite current collector may include a polymer material base and a metal layer formed on at least one surface of the polymer material base. The composite current collector may be formed by forming a metal material (aluminum, aluminum alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy, etc.) on a polymer material substrate (such as a substrate of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE), etc.).
[0104] In some embodiments, when the secondary battery is a lithium-ion battery, the positive electrode active material may adopt a positive electrode active material for lithium-ion batteries that is well known in the art. As an example, the positive electrode active material may include at least one of the following materials: a lithium-containing phosphate with an olivine structure, a lithium transition metal oxide, and their respective modified compounds. However, the present application is not limited to these materials, and other traditional materials that can be used as positive electrode active materials for batteries may also be used. These positive electrode active materials may be used alone or in combination of two or more. Among them, examples of lithium transition metal oxides may include, but are not limited to, lithium cobalt oxide (such as LiCoO2), lithium nickel oxide (such as LiNiO2), lithium manganese oxide (such as LiMnO2, LiMn2O4), lithium nickel cobalt oxide, lithium manganese cobalt oxide, lithium nickel manganese oxide, lithium nickel cobalt manganese oxide (such as LiNi 1 / 3 Co 1 / 3Mn 1 / 3 O2 (also referred to as NCM333), LiNi 0.5 Co 0.2 Mn 0.3 O2 (also referred to as NCM523), LiNi0.5 Co 0.25 Mn 0.25 O2 (also referred to as NCM211), LiNi 0.6 Co 0.2 Mn 0.2 O2 (also referred to as NCM622), LiNi 0.8 Co 0.1 Mn 0.1 O2 (also referred to as NCM811), lithium nickel cobalt aluminum oxide (such as LiNi 0.85 Co 0.15 Al 0.05 O2) and its modified compounds, etc. Examples of lithium-containing phosphates with an olivine structure may include, but are not limited to, at least one of lithium iron phosphate (such as LiFePO4 (also referred to as LFP)), a composite material of lithium iron phosphate and carbon, lithium manganese phosphate (such as LiMnPO4), a composite material of lithium manganese phosphate and carbon, lithium iron manganese phosphate, and a composite material of lithium iron manganese phosphate and carbon.
[0105] In some embodiments, the positive electrode film layer may further optionally include a binder. As an example, the binder may include at least one of polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), vinylidene fluoride-tetrafluoroethylene-propylene terpolymer, vinylidene fluoride-hexafluoropropylene-tetrafluoroethylene terpolymer, tetrafluoroethylene-hexafluoropropylene copolymer, and fluorine-containing acrylate resin.
[0106] In some embodiments, the positive electrode film layer may further include a conductive agent, which may include, for example, at least one of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers.
[0107] In some embodiments, the positive electrode sheet can be prepared in the following manner: the components for preparing the positive electrode sheet, such as the positive electrode active material, the conductive agent, the binder and any other components are dispersed in a solvent (such as N-methylpyrrolidone) to form a positive electrode slurry; the positive electrode slurry is coated on the positive electrode collector, and after drying, cold pressing and other processes, the positive electrode sheet can be obtained.
[0108] In a fourth aspect, an embodiment of the present application provides a battery, comprising the electrode sheet of the third aspect of the present application.
[0109] In any embodiment, the battery comprises a primary battery or a secondary battery.
[0110] Generally, a secondary battery includes a positive electrode, a negative electrode, an electrolyte, and a separator. During the battery charging and discharging process, active ions are embedded and removed back and forth between the positive electrode and the negative electrode. The electrolyte plays the role of conducting ions between the positive electrode and the negative electrode. The separator is set between the positive electrode and the negative electrode, mainly to prevent the positive and negative electrodes from short-circuiting, while allowing ions to pass through.
[0111] In some embodiments, the secondary battery further includes a separator. The present application has no particular limitation on the type of separator, and any known porous separator with good chemical stability and mechanical stability can be selected.
[0112] In some embodiments, the material of the isolation membrane can be selected from at least one of glass fiber, non-woven fabric, polyethylene, polypropylene and polyvinylidene fluoride. The isolation membrane can be a single-layer film or a multi-layer composite film, without particular limitation. When the isolation membrane is a multi-layer composite film, the materials of each layer can be the same or different, without particular limitation.
[0113] In some embodiments, the positive electrode sheet, the negative electrode sheet, and the separator may be formed into an electrode assembly by a winding process or a lamination process.
[0114] In some embodiments, the secondary battery may include an outer package, which may be used to encapsulate the electrode assembly and the electrolyte.
[0115] In some embodiments, the outer packaging of the secondary battery may be a hard shell, such as a hard plastic shell, an aluminum shell, a steel shell, etc. The outer packaging of the secondary battery may also be a soft package, such as a bag-type soft package. The material of the soft package may be plastic, and examples of the plastic include polypropylene, polybutylene terephthalate, and polybutylene succinate.
[0116] The present application has no particular limitation on the shape of the secondary battery, which may be cylindrical, square or any other shape. Figure 1 The secondary battery 5 is a square structure as an example.
[0117] In some embodiments, reference Figure 2 , the outer packaging may include a shell 51 and a cover plate 53. Among them, the shell 51 may include a bottom plate and a side plate connected to the bottom plate, and the bottom plate and the side plate enclose a receiving cavity. The shell 51 has an opening connected to the receiving cavity, and the cover plate 53 can be covered on the opening to close the receiving cavity. The positive electrode sheet, the negative electrode sheet and the isolation film can form an electrode assembly 52 through a winding process or a lamination process. The electrode assembly 52 is encapsulated in the receiving cavity. The electrolyte is infiltrated in the electrode assembly 52. The number of electrode assemblies 52 contained in the secondary battery 5 can be one or more, and those skilled in the art can choose according to specific actual needs.
[0118] In some embodiments, secondary batteries may be assembled into a battery module. The number of secondary batteries contained in the battery module may be one or more, and the specific number may be selected by those skilled in the art according to the application and capacity of the battery module.
[0119] Figure 3 4 is an example of a battery module. Figure 3 In the battery module 4, the plurality of secondary batteries 5 may be arranged in sequence along the length direction of the battery module 4. Of course, they may also be arranged in any other manner. Further, the plurality of secondary batteries 5 may be fixed by fasteners.
[0120] Optionally, the battery module 4 may further include a housing having a receiving space, and the plurality of secondary batteries 5 are received in the receiving space.
[0121] In some embodiments, the battery modules described above may also be assembled into a battery pack. The battery pack may contain one or more battery modules, and the specific number may be selected by those skilled in the art according to the application and capacity of the battery pack.
[0122] Figure 4 and Figure 5 1 is a battery pack 1 as an example. Figure 4 and Figure 5 The battery pack 1 may include a battery box and a plurality of battery modules 4 disposed in the battery box. The battery box includes an upper box body 2 and a lower box body 3. The upper box body 2 can cover the lower box body 3 and form a closed space for accommodating the battery modules 4. The plurality of battery modules 4 can be arranged in the battery box in any manner.
[0123] In a fifth aspect, an embodiment of the present application proposes an electrical device, including the electrochemical device of the fourth aspect of the present application.
[0124] In addition, the present application also provides an electrical device, which includes at least one of the secondary battery, battery module, or battery pack provided in the present application. The secondary battery, battery module, or battery pack can be used as a power source for the electrical device, and can also be used as an energy storage unit for the electrical device. The electrical device may include mobile devices (such as mobile phones, laptops, etc.), electric vehicles (such as pure electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles, electric bicycles, electric scooters, electric golf carts, electric trucks, etc.), electric trains, ships and satellites, energy storage systems, etc., but are not limited thereto.
[0125] As the electrical device, a secondary battery, a battery module or a battery pack may be selected according to its usage requirements.
[0126] Figure 6The power consumption device is taken as an example. The power consumption device is a pure electric vehicle, a hybrid electric vehicle, or a plug-in hybrid electric vehicle. In order to meet the high power and high energy density requirements of the power consumption device for the secondary battery, a battery pack or a battery module can be used.
[0127] Another example of a device may be a mobile phone, a tablet computer, a notebook computer, etc. Such a device is usually required to be thin and light, and a secondary battery may be used as a power source.
[0128] Example
[0129] Hereinafter, the embodiments of the present application will be described. The embodiments described below are exemplary and are only used to explain the present application, and should not be construed as limiting the present application. If no specific techniques or conditions are indicated in the embodiments, the techniques or conditions described in the literature in this area or the product specifications are used. If the manufacturer is not indicated in the reagents or instruments used, they are all conventional products that can be obtained commercially.
[0130] The parameters of the electrode materials of Examples 1 to 23 and Comparative Examples 1 to 4 of the present application are as shown in Table 1.
[0131]
[0132]
[0133] Embodiment 24
[0134] A method for preparing a positive electrode material comprises the following steps:
[0135] A sodium alginate polymer coating layer is formed on the outside of the lithium manganese oxide to obtain a positive electrode material.
[0136] Embodiment 25
[0137] A method for preparing a negative electrode material comprises the following steps:
[0138] A sodium alginate polymer coating layer is formed on the outside of the graphite to obtain a negative electrode material.
[0139] Embodiment 26
[0140] A method for preparing a positive electrode material comprises the following steps:
[0141] The sodium alginate solution is mixed with lithium manganate, and a coating layer is formed on the surface of the lithium manganate by polymerization reaction to obtain a positive electrode material.
[0142] Embodiment 27
[0143] A method for preparing a positive electrode material comprises the following steps:
[0144] The sodium alginate solution was mixed with lithium manganate, and a polymerization reaction was carried out at 25° C. for 1.5 h on the surface of the lithium manganate to form a coating layer to obtain a positive electrode material.
[0145] Performance Test:
[0146] The electrode materials of Examples 1 to 23 and Comparative Examples 1 to 4 were prepared into secondary batteries, wherein the preparation method is as follows:
[0147] 1) Cathode slurry
[0148] The positive electrode materials of Examples 1 to 17 and Comparative Examples 1 to 2, the binder PVDF, the conductive agent carbon black, and the CNT were dry mixed in a ratio of 96:2:1.7:0.3 for 15 minutes, and then NMP was added and stirred at 1000 rpm for 120 minutes to finally obtain a uniform positive electrode slurry with a solid content of 70%;
[0149] Cathode sheet preparation
[0150] The positive electrode slurry is evenly coated on the positive electrode current collector aluminum foil, and the coating mass is 0.015g / cm 2 The oven temperature is set to 130°C to dry the electrode sheet; then the positive electrode sheet is obtained through processes such as cold pressing, slitting, and welding the electrode ears.
[0151] Battery components and finished product preparation
[0152] The negative electrode material hard carbon, the conductive agent acetylene black, the binder styrene butadiene rubber (SBR), and the thickener sodium carboxymethyl cellulose (CMC) are fully stirred and mixed in a deionized water solvent system at a mass ratio of 96.8:0.4:1.7:1.1, and then coated on the negative electrode current collector copper foil. After drying, the negative electrode sheet is obtained by cold pressing, slitting and other processes.
[0153] Isolation film: Use PE isolation film;
[0154] The electrolyte is a 1.2 mol / L lithium hexafluorophosphate salt solution, and the organic solvent is an electrolyte prepared by ethylene carbonate (EC), diethyl carbonate (DEC), and dimethyl carbonate (DMC) in a volume ratio of 5:2:3;
[0155] The positive electrode sheet, the separator, and the negative electrode sheet were assembled in a dry environment with a humidity of less than 2%, and after drying, the electrolyte was injected and packaged. A soft-pack battery with a capacity of 2.1Ah was prepared through a formation test, and an electrical performance test was performed.
[0156] 2) Negative electrode slurry
[0157] The negative electrode materials of Examples 18 to 23 and Comparative Examples 3 to 4, conductive agent acetylene black, binder styrene butadiene rubber (SBR), and thickener sodium carboxymethyl cellulose (CMC) were fully stirred and mixed in a deionized water solvent system at a mass ratio of 96.8:0.4:1.7:1.1 to obtain a uniform negative electrode slurry.
[0158] Negative electrode preparation
[0159] The negative electrode slurry is evenly coated on the negative electrode current collector aluminum foil, and the coating mass is 0.01g / cm 2 The oven temperature is set to 130°C to dry the electrode sheet; then the negative electrode sheet is obtained through processes such as cold pressing, slitting, and welding the electrode ears.
[0160] Battery components and finished product preparation
[0161] The positive electrode material, binder PVDF, conductive agent carbon black, and CNT were dry mixed in a ratio of 96:2:1.7:0.3 for 15 minutes, and NMP was added and stirred at 1000 rpm for 120 minutes to finally obtain a uniform positive electrode slurry with a solid content of 70%. The positive electrode slurry was evenly coated on the positive electrode current collector aluminum foil with a coating mass of 0.015 g / cm 2 The oven temperature is set to 130°C to dry the electrode sheet; then the positive electrode sheet is obtained through processes such as cold pressing, slitting, and welding the electrode ears.
[0162] Isolation film: Use PE isolation film.
[0163] The electrolyte is a 1.2 mol / L lithium hexafluorophosphate salt solution, and the organic solvent is ethylene carbonate (EC), diethyl carbonate (DEC), and dimethyl carbonate (DMC) in a volume ratio of 5:2:3 to prepare the electrolyte.
[0164] The positive electrode sheet, the separator, and the negative electrode sheet were assembled in a dry room environment with a humidity of less than 2%, dried, filled with the corresponding electrolyte, and packaged. A soft-pack battery with a capacity of 2.1Ah was prepared through a formation test, and an electrical performance test was performed.
[0165] Perform the following test:
[0166] At 45°C, the assembled battery was charged to 4.2V at 0.5C, left for 10 minutes, and then discharged to 2.5V at 1C. The above steps were repeated for the same battery, and the battery capacity after 800 cycles was recorded. The results are shown in Table 1.
[0167] As can be seen from Table 1, through Examples 1 to 23 and Comparative Examples 1 to 4, it can be seen that by forming a polymer coating layer on the surface of the electrode active material, the direct contact between the electrode active material and the electrolyte can be reduced, and the polymer monomer can spontaneously form a polymer, which greatly reduces the production cost. In addition, since the polymer is a chemical bond, it is more stable, which improves the stability of the coating layer and the core active material structure, thereby improving the cycle performance of the battery.
[0168] It can be seen from Examples 1 to 7 that a coating layer with a mass percentage of 0.05% to 1% in the electrode material is beneficial to the rapid transmission of ions and electrons in the electrode material, reduces the impact on the battery energy density, and reduces the direct contact between the active material and the electrolyte.
[0169] It can be seen from Examples 4 and 8 to 13 that different polymer monomers can allow carboxyl groups and hydroxyl groups to spontaneously form ion-conducting polymers, thereby achieving in-situ coating of electrode active materials, thereby coating the electrode active materials in the coating layer, thereby reducing the contact between the electrode active materials and the electrolyte, thereby reducing the reaction between the electrode active materials and the electrolyte and improving the cycle performance of the battery.
[0170] It can be seen from Examples 14 to 17 that the amino groups and hydroxyl groups in the polymers formed by different amino groups and hydroxyl groups spontaneously form ion-conducting polymers, thereby achieving in-situ coating of the electrode active materials, thereby coating the electrode active materials in the coating layer, thereby reducing the contact between the electrode active materials and the electrolyte, thereby reducing the reaction between the electrode active materials and the electrolyte, and improving the cycle performance of the battery.
[0171] It can be seen from Examples 17 to 23 that both the negative electrode active material and the positive electrode active material can form a polymer-coated coating structure, thereby reducing the direct contact between the active material and the electrolyte and improving the cycle performance of the battery. In addition, the compounds containing different multivalent metal ions can provide coordination bonds for the polymerization of polymer monomers, and the compounds containing different multivalent metal ions can be in the core or in the coating.
[0172] In summary, in the electrode material proposed in the present application, by setting the electrode material into a core-shell structure, through the polymer monomer, the carboxylate functional group and the carboxyl group can spontaneously form an ion-conducting polymer, thereby realizing the in-situ coating of the electrode active material, thereby coating the electrode active material in the coating layer, thereby reducing the contact between the electrode active material and the electrolyte, thereby reducing the reaction between the electrode active material and the electrolyte, and improving the cycle performance of the battery. Or by the polymer monomer including an amino group and a hydroxyl group, wherein the amino group and the hydroxyl group spontaneously form an ion-conducting polymer, thereby realizing the in-situ coating of the electrode active material, thereby coating the electrode active material in the coating layer, thereby reducing the contact between the electrode active material and the electrolyte, thereby reducing the reaction between the electrode active material and the electrolyte, and improving the cycle performance of the battery. In the present application, a stable chemical bond is formed between the coating layers, and the structure of the coating layer and the inner core is more stable, which improves the stability of the structure of the coating layer and the inner core active material.
[0173] It should be noted that the present application is not limited to the above-mentioned embodiments. The above-mentioned embodiments are only examples, and the embodiments having the same structure as the technical idea and exerting the same effect within the scope of the technical solution of the present application are all included in the technical scope of the present application. In addition, without departing from the scope of the main purpose of the present application, various modifications that can be thought of by those skilled in the art to the embodiments and other methods of combining some of the constituent elements in the embodiments are also included in the scope of the present application.
Claims
1. An electrode material, characterized in that: The invention comprises a core and a coating layer at least partially coated on the surface of the core, wherein the core comprises an electrode active material, and the coating layer comprises a polymer mainly formed of at least one polymer monomer; Wherein, the polymer monomer includes a carboxyl group and a hydroxyl group; or, the polymer monomer includes an amino group and a hydroxyl group.
2. The electrode material according to claim 1, characterized in that The polymer monomers include carboxyl groups and hydroxyl groups, wherein: The number of the carboxyl groups is m1, m1 is a positive integer from 1 to 5; optionally, m1 is a positive integer from 1 to 3; and / or, The number of the hydroxyl groups is n1, and n1 is a positive integer of 1-7; optionally, n1 is a positive integer of 3-5.
3. The electrode material according to claim 2, characterized in that The polymer monomer includes at least one of sodium alginate, (1-pyrenyl)-BD-glucuronide, D-galacturonic acid and glycyrrhizic acid.
4. The electrode material according to claim 1, characterized in that The polymer monomers include amino groups and hydroxyl groups, wherein: The number of the amino groups is m2, where m2 is a positive integer from 1 to 5; optionally, m2 is a positive integer from 2 to 3; and / or, The number of the hydroxyl groups is n2, where n2 is a positive integer of 1 to 6; optionally, n2 is a positive integer of 2 to 4.
5. The electrode material according to claim 4, characterized in that The polymer monomer includes at least one of diglycolamine, 1-amino-3-ethoxy-2-propanol, naphthol AS-BI N-acetyl-β-D-aminoglucosidoside and 1-[2-(2-hydroxyethoxy)ethyl]piperazine.
6. The electrode material according to any one of claims 1 to 5, characterized in that The electrode material includes a compound containing multivalent metal ions.
7. The electrode material according to claim 6, characterized in that The compound containing multivalent metal ions includes a compound containing at least one of iron ions, aluminum ions, manganese ions and nickel ions.
8. The electrode material according to any one of claims 1 to 7, characterized in that The electrode material is a positive electrode material, wherein the material of the core at least includes lithium manganese oxide.
9. The electrode material according to claim 8, characterized in that Lithium manganate includes doped lithium manganate, and the molecular formula of doped lithium manganate includes LiMn 2-α X α O4; Wherein, X includes at least one of magnesium, cobalt, nickel, chromium, iron and titanium. The value of α is 0.001~0.
5.
10. The electrode material according to any one of claims 1 to 9, characterized in that The mass fraction of the coating layer is w1, and the mass fraction of the core is w2, wherein, 0.05%≤w1:(w1+w2)≤1%; optionally, 0.1%≤w1:(w1+w2)≤0.5%.
11. The method for preparing an electrode material according to any one of claims 1 to 10, characterized in that: The following steps are involved: Forming a coating layer outside the inner core, wherein the coating layer is formed with a polymer formed from at least one polymer monomer, to obtain an electrode material; Wherein, the polymer monomer includes a carboxyl group and a hydroxyl group; or, the polymer monomer includes an amino group and a hydroxyl group.
12. The method for preparing an electrode material according to claim 11, characterized in that: The step of forming a coating layer outside the core, wherein the coating layer is formed with a polymer formed from at least one polymer monomer, and obtaining the electrode material comprises: The polymer monomer is polymerized on the surface of lithium manganate to form a coating layer to obtain an electrode material.
13. The method for preparing an electrode material according to claim 12, characterized in that: The step of polymerizing the polymer monomer on the surface of lithium manganate to form a coating layer to obtain an electrode material comprises: The sodium alginate solution is mixed with lithium manganate, and a coating layer is formed on the surface of the lithium manganate by polymerization reaction to obtain an electrode material.
14. The method for preparing an electrode material according to claim 12 or 13, characterized in that: The polymerization reaction time is 0.5 to 5 hours; optionally, the polymerization reaction time is 1 to 2 hours; and / or, The polymerization reaction temperature is 10-45°C; optionally, the polymerization reaction time is 20-35°C.
15. An electrode sheet, characterized in that: The invention comprises an electrode material as claimed in claims 1 to 10 or an electrode material prepared by the method for preparing the electrode material as claimed in claims 11 to 14.
16. A battery, characterized in that: Comprising the electrode sheet as claimed in claim 15.
17. An electrical device, characterized in that: Comprising the battery of claim 16.